ADOLESCÊNCIA E PARTICIPAÇÃO SOCIAL: CONSIDERAÇÕES SOBRE O PROJETO MENARCA DE PROMOÇÃO À SAÚDE DA MENINA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
The aim of this research is to relate the themes adolescence and social participation based on the history and experiences narrated by the members of the Menarche Project and Promotion of Girls´ Health in the city of Ponta Grossa, Paraná, Brazil from 2002 to 2007. Considering memory data, the narratives were produced according to a methodological procedure used in oral history. The testimonies allowed the construction of the Menarche Project history, its changes, development, methodology and social scope. The research report is divided into two chapters: the first one presents a literature review about health promotion, highlighting the changes in the assistance of adolescents´ health and the sociopolitical context that stimulated specific public policies to this age group. The second chapter presents seven testimonies articulated to the National Curricular Guidelines, Health Project and Promotion in Schools, and Health Promotion Policies. The education methodology between pairs is also articulated with the testimonies, presented as an intervention process and form of socialization common in adolescence.
Keywords: adolescência; participação social; Projeto Menarca; adolescence; social participation; Menarche project; CNPQ::CIENCIAS SOCIAIS APLICADAS